The influence of job satisfaction and organizational commitment on turnover intention - Siti Nuraftnahanim, Alias (2019)
Employees turnover is an endless issue and has been studied many years ago and found that turnover intention is the predictor to actual turnover. There are many factors that could influence employee’s intention to leave their organization. Although many researches have been conducted studies on turnover intention, job satisfaction as well as organizational commitment, but there is still insufficient data related to relationship between turnover intention, job satisfaction and organizational commitment particularly in the context of retail industry. Thus, the purpose of this study is to determine the relationship between job satisfaction and turnover intention as well as organizational commitment and turnover intention among retail employees. A convenience sampling technique was used for data collection, questionnaire were conveniently distributed to several retail stores located in Kota Kinabalu, Sabah. The total no of 227 retail employee responded and return their answer. Distributed questionnaire consist of three instruments, turnover intention question which consist of 3 question, Minnesota Satisfaction Questionnaire (MSQ) used to measured job satisfaction the last instrument to measured organizational commitment of the employees. There are several analyses been used in this study include descriptive analysis used for respondent’s profile, Pearson Correlation analysis used to determine the relationship between job satisfaction with turnover intention and organization commitment with turnover intention. Whereas Multiple Regression analysis used to examine whether job satisfaction. Organizational commitment influence turnover intention. Wishfully, the present study can provide more understanding on turnover intention, job satisfaction and organizational commitment particularly done in retail industry.